2011
DOI: 10.1111/j.1750-8606.2011.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Exergames for Physical Education Courses: Physical, Social, and Cognitive Benefits

Abstract: Digital games combining exercise with game play, known as exergames, can improve youths’ health status and provide social and academic benefits. Exergame play increases caloric expenditure, heart rate, and coordination. Psychosocial and cognitive impacts of exergame play may include increased self-esteem, social interaction, motivation, attention, and visual–spatial skills. This article summarizes the literature on exergames, with a special emphasis on physical education courses and the potential of exergames … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
228
0
33

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 328 publications
(265 citation statements)
references
References 32 publications
(35 reference statements)
4
228
0
33
Order By: Relevance
“…Most exergamers played at home, although many also played at friends' homes. Although exergaming at school is associated with improvements in academic behavior and achievement, [65][66][67] AdoQuest participants rarely exergamed at school.…”
Section: Discussionmentioning
confidence: 99%
“…Most exergamers played at home, although many also played at friends' homes. Although exergaming at school is associated with improvements in academic behavior and achievement, [65][66][67] AdoQuest participants rarely exergamed at school.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exergaming on age-related impaired postural control have been examined in some studies [16,17,19]. The results showed a significant improvement in balance while walking, which was the main parameter measured by tasks such as the Community Balance and Mobility Scale, the Berg Balance Scale and narrow walk time [16][17][18][19][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that exergaming that increased physical activity in geriatric patients with a high risk of falling or with cardiovascular diseases was practical and safe [15][16][17][18][19][20]. The effects of exergaming on age-related impaired postural control have been examined in some studies [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations